2012 IEEE 23rd International Conference on Application-Specific Systems, Architectures and Processors 2012
DOI: 10.1109/asap.2012.16
|View full text |Cite
|
Sign up to set email alerts
|

A Speed Area Optimized Embedded Co-processor for McEliece Cryptosystem

Abstract: Abstract-This paper describes the systematic design methods of an embedded co-processor for a post quantum secure McEliece cryptosystem. A hardware/software co-design has been targeted for the realization of McEliece in practice on low-cost embedded platforms. Design optimizations take place when choosing system parameters, algorithm transformations, architecture choices, and arithmetic primitives. The final architecture consists of an 8-bit PicoBlaze softcore for flexibility and several parallel acceleration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…A McEliece co-processor was recently proposed for a Virtex5-LX110T FPGA [16]. Their design goal was to optimize the speed/area ratio while we aim for high performance.…”
Section: Fpga Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A McEliece co-processor was recently proposed for a Virtex5-LX110T FPGA [16]. Their design goal was to optimize the speed/area ratio while we aim for high performance.…”
Section: Fpga Resultsmentioning
confidence: 99%
“…This is particularly considered an issue for small and embedded systems where memory and processing power are a scarce resource. Nevertheless, it was shown that code-based cryptosystems such as the well-established proposals by McEliece and Niederreiter can significantly outperform classical asymmetric cryptosystems on embedded systems [13,16,20,32] -at the cost of very large keys (often more than 50 kByte). Therefore, current research is targeting alternative codes that allow more compact key representations but still preserve the security properties of the cryptosystem.…”
Section: Introductionmentioning
confidence: 99%
“…However, the private key size of Niederreiter scheme is a bottleneck in practice, and McEliece is one step ahead in that respect. There are few existing implementations available in the literature for computing McEliece cryptosystems with 80-bit and 103-bit security [4][5][6][7]. The only work [3] proposed a 128-bit secure McEliece cryptosystem, which has taken also into account the latest CCA2 security and the countermeasures against the state of the art sidechannel attacks on this scheme.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the closest works on this subject are hardware implementations on generic Goppa codes [9] [10] [11] [12] which, albeit compatible with QD-Goppa codes, are unable to take full advantage of their specific structure. Aiming to assess these advantages of QD-Goppa codes over their generic counterparts, in this article we describe a flexible design and implementation of such codes for use in cryptographic schemes.…”
Section: Introductionmentioning
confidence: 99%